2019
DOI: 10.1021/acsabm.9b00694
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Detection of Mutant β-Amyloid(1–40) Membrane-Active Aggregation with Biosensing Vesicles

Abstract: Alzheimer’s disease (AD) is a protein misfolding disease commonly characterized by neuritic amyloid plaques and proteinaceous fibrillar aggregate deposits composed of β-amyloid (Aβ) aggregates. The dynamic aggregation of Aβ forms toxic, nanoscale aggregate species which proceed from oligomers to fibrils. Currently, there is need for rapid and direct detection of Aβ peptide aggregation and interaction with lipid membranes, as detecting an interaction with various lipid environments will provide insights to bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Figure a shows the PL response of the anti-NSE/amine-N-GQDs@AuNPs nanocomplex for the different NSE antigen concentrations (0.1 pg mL –1 to 1000 ng mL –1 ). Fluorescence intensity of anti-NSE/amine-N-GQDs conjugate was found to recover linearly with increasing NSE antigen concentration (Figure b) and can be described by the eq : The PL intensity recovery can be attributed to the formation of immunocomplex arising due to the specific interaction of NSE antigen with anti-NSE antibody, which increases the distance between anti-NSE/amine-N-GQDs donor and AuNPs quencher resulting in the obstruction of the energy transfer process and hence gradual recovery of fluorescence. , Further, the limit of detection (LOD) was found to be 0.09 pg mL –1 calculated using the eq : where σ is the standard deviation, and S is the sensitivity of the fluorescent biosensor calculated using the slope of the calibration curve.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a shows the PL response of the anti-NSE/amine-N-GQDs@AuNPs nanocomplex for the different NSE antigen concentrations (0.1 pg mL –1 to 1000 ng mL –1 ). Fluorescence intensity of anti-NSE/amine-N-GQDs conjugate was found to recover linearly with increasing NSE antigen concentration (Figure b) and can be described by the eq : The PL intensity recovery can be attributed to the formation of immunocomplex arising due to the specific interaction of NSE antigen with anti-NSE antibody, which increases the distance between anti-NSE/amine-N-GQDs donor and AuNPs quencher resulting in the obstruction of the energy transfer process and hence gradual recovery of fluorescence. , Further, the limit of detection (LOD) was found to be 0.09 pg mL –1 calculated using the eq : where σ is the standard deviation, and S is the sensitivity of the fluorescent biosensor calculated using the slope of the calibration curve.…”
Section: Resultsmentioning
confidence: 99%
“…The PL intensity recovery can be attributed to the formation of immunocomplex arising due to the specific interaction of NSE antigen with anti-NSE antibody, which increases the distance between anti-NSE/amine-N-GQDs donor and AuNPs quencher resulting in the obstruction of the energy transfer process and hence gradual recovery of fluorescence. 48,49 Further, the limit of detection (LOD) was found to be 0.09 pg mL −1 calculated using the eq 6:…”
Section: Energy Transfer Betweenmentioning
confidence: 99%
“…It is at these interfaces that they start to self-assemble and the relative affinities of the various protein species (monomeric vs. oligomeric) for the interface and the extent to which the interfacially-associated monomer lowers the free energy barrier for nucleation determine how quickly primary heterogeneous nucleation can begin. Recent studies have shown that certain amyloidogenic IDPs, including tau, TDP-43, and -synuclein, can phase-separate from the aqueous solution, producing protein droplets, both in vitro and in vivo [76][77][78]. In such an environment, amyloid aggregation is a highly favorable process.…”
Section: Primary Nucleation Pathwaymentioning
confidence: 99%
“…Recently, Dorsey and coworkers (2019) [22] also studied the interaction of Aβ 1–42 in the presence of various lipids. Three biomimetic systems composed of polydiacetylene (PDA) and BTLE (neutral extract), 1,2‐dimyristoyl‐sn‐glycero‐3‐phosphocholine (DMPC) (zwitterionic phospholipid) or 1,2‐dimyristoyl‐sn‐glycero‐3‐phosphoglycerol (DMPG) (anionic phospholipid) were used for this purpose.…”
Section: Factors Modulating Aβ‐lipid Membrane Interactionsmentioning
confidence: 99%